Influence of hairy vetch seed germination and maturation on weediness in subsequent crops. (13th September 2019) - Pittman, K B; Barney, J N; Cahoon, C W; Flessner, M L
Summary: Hairy vetch is a widely adopted cover crop in the United States. However, hairy vetch can become weedy in subsequent crops as seeds germinate after the cover crop growing season, which is largely attributed to seed dormancy. We conducted two field experiments to determine seed germination, viability and seed production phenology of two common hairy vetch cultivars in Blacksburg and Blackstone, Virginia, US. 'Groff' and 'Purple Bounty' seed were sown in October 2015 and May 2016 and germination was tracked until June 2017. Subsequently, ungerminated seeds were tested for viability. Both cultivars had <2% germination after the initial germination period, and <1% of seed recovered was still viable at the end of the experiments. We also conducted experiments to determine when these cultivars produce viable seed. Hairy vetch seeds were counted and tested for germination in the spring. Both cultivars produced seed beginning in late‐May, but most seed were not viable until mid‐June in Virginia. Our results indicate that seed dormancy is not the primary cause of hairy vetch weediness in subsequent crops as nearly all germination, 99% of the total germinated seed, occurred during the cover crop growing season. Also, if complete termination occurs before mid‐June in Virginia, it is unlikely viable seed will be added to the seed bank. To better utilise this cover crop species, cultivar selection and proper termination are important to prevent weediness.